KONSEP PEMBANGUNAN EKONOMI BERBASIS ISLAM (Sebuah Upaya Pembangunan Ekonomi Indonesia yang Adil, Makmur, dan Sejahtera) - Fadlan Fadlan (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2010)
Abstract: Islam anticipates  economic developmen, however it still consider as a part of the development of human being as the greatest one. The essence is that human being enables to control the economic environment as well as to improve the life quality. There are four basic Islamic teachings dealing with the philosphy of Islamic economic development:  tawhîd, rubûbiyah, khalîfah and tazkiyah. The principle of  tauhîd is to prevent a concentrated economy power.  khalîfah principle is to guard against environmet damage and to protect natural sources conservation. The principle of  tazkiyah to prohibit social imbalance and to realize equality and justice. Accordingly, it can give shape to a continuity development. The concept of continuity development is essentially the implementation of the principle of rubûbiyah, it is the priciple of education, maintenance, and continuity to the perfectness, as the principle of  divinity (ilahi). Hence, if the four principles are realized in the Indonesian economic development, government will easily create the nation’s ambition, a prosperous and justice nation.   Key Words: ekonomi Islam, homo economicus, dan pembangunan ekonomi